Formation mechanism for the laying angle of hemp harvester based on ANSYS-ADAMS - Huang, Jicheng; Tan, Li; Tian, Kunpeng; Zhang, Bin; Ji, Aimin; Liu, Haolu; Shen, Cheng (International Journal of Agricultural and Biological Engineering, 2023)
Aiming at the problem of large differences in the laying angle and posture of plants cut by the hemp harvester, which is unfavorable for the subsequent picking-up, this paper analyzed the laying process and laying angles, and built a conveyor-plant rigid-flexible coupling model for simulating the laying of hemp plant. Moreover, the operating parameters were tested and optimized based on the central composite design theory, and carried out multi-objective optimization with the minimum laying angle as the response index. Firstly, the formation mechanism of the laying angle of hemp harvester was studied. Secondly, a test was designed with the quadratic orthogonal rotational combination test method, with the data being processed by Design-Expert. A regression mathematical model of the laying angle was built, and the influence of the interactions between factors on the laying angle was analyzed with the response surface method. Furthermore, multi-objective optimization was conducted on the regression model according to the actual production design requirements. As a result, the best combination was obtained, that is, when the forward speed is 0.7 m/s, speed ratio 1.40, and stubble height 95 mm, the minimum laying angle can be obtained, namely 124.9°. The optimization parameters were verified by the simulation and field tests. The simulation test showed that the simulated laying angle is 125.2°, with a relative error of 0.24% from the theoretical value, under the best combination of parameters. The field test showed that the average laying angle of hemp plant is 121.8°, with a relative error of 2.5% from the theoretical value, under the best combination of parameters. The results may provide a reference for the structural improvement and operating parameter control of hemp harvesters. Keywords: agricultural machinery, hemp, laying angle, rigid-flexible coupling model, optimization, response surface analysis DOI: 10.25165/j.ijabe.20231604.7978 Citation: Huang J C, Tan L, Tian K P, Zhang B, Ji A M, Liu H L, Shen C. Formation mechanism for the laying angle of hemp harvester based on ANSYS-ADAMS. Int J Agric & Biol Eng, 2023; 16(4): 109–115.